Slovak Republic : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This report on the Observance of Standards and Codes (ROSC)-data module-provides an assessment of the Slovak Republic's macroeconomic statistics against the Special Data Dissemination Standard (SDDS), complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that statistical agencies in the Slovak Republic generally have a legal and institutional framework that supports statistical quality, although the formal legal mandate to disseminate statistics should be made explicit. Resources are generally adequate for existing statistical programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet